Presynaptic Membrane Receptors Modulate ACh Release, Axonal Competition and Synapse Elimination during Neuromuscular Junction Development - Tomàs, Josep; Garcia, Neus; Lanuza, Maria A.; Santafé, Manel M.; Tomàs, Marta; Nadal, Laura; Hurtado, Erica; Simó, Anna; Cilleros, Víctor (Frontiers in Molecular Neuroscience, 2017)
The development of the nervous system involves an initially exuberant production of neurons, which establish an excessive number of synapses, and the subsequent reduction in both neurons and synaptic contacts as maturation proceeds. Hebbian competition between axons with different activities leads to the loss of roughly half of the neurons initially produced so connectivity is refined and specificity gained. The skeletal muscle fibers in the newborn neuromuscular junction (NMJ) are polyinnervated by several motor axons but by the end of the axonal competition, two weeks later, the endplates are innervated by a single axon. This peripheral synapse has long been used as a convenient model for synapse development. In the last few years, we have studied transmitter release and the local involvement of the presynaptic muscarinic ACh autoreceptors (mAChR), adenosine autoreceptors (AR) and trophic factor receptors (TFR, for neurotrophins and trophic cytokines) during the development of NMJ and in the adult. This review brings together previously published data and proposes a molecular background for developmental axonal competition and loss. At the end of the first week postnatal, these receptors modulate transmitter release in the various nerve terminals on polyinnervated NMJ and contribute to axonal competition and synapse elimination.